A Clinical Predictive Model for One-year Colectomy in Adults Hospitalized for Severe Ulcerative Colitis. Issue 1 (21st December 2021) - Zafer, Maryam; Zhang, Hui; Dwadasi, Sujaata; Goens, Donald; Paknikar, Raghavendra; Dalal, Sushila; Cohen, Russell D; Pekow, Joel; Rubin, David T; Sakuraba, Atsushi; Micic, Dejan
Abstract: Background: Models to predict colectomy in ulcerative colitis (UC) are valuable for identification, clinical management, and follow-up of high-risk patients. Our aim was to develop a clinical predictive model based on admission data for one-year colectomy in adults hospitalized for severe UC. Methods: We performed a retrospective analysis of patients hospitalized at a tertiary academic center for management of severe UC from 1/2013 to 4/2018. Multivariate regression was performed to identify individual predictors of one-year colectomy. Outcome probabilities of colectomy based on the prognostic score were estimated using a bootstrapping technique. Results: Two hundred twenty-nine individuals were included in the final analytic cohort. Four independent variables were associated with one-year colectomy which were incorporated into a point scoring system: (+) 1 for single class biologic exposure prior to admission; (+) 2 for multiple classes of biologic exposure; (+) 1 for inpatient salvage therapy with cyclosporine or a TNF-alpha inhibitor; (+) 1 for age <40. The risk probabilities of colectomy within one year in patients assigned scores 1, 2, 3, and 4 were 9.4% (95% CI, 1.7–17.2), 33.7% (95% CI, 23.9–43.5), 58.5% (95% CI, 42.9–74.1), 75.0% (95% CI, 50.5–99.5). An assigned score of zero was a perfect predictor of no colectomy. Conclusion: Risk factors most associated with one-year colectomy for severe UC included: prior biologic exposure, need for inpatient salvage therapy, and younger age. We developed a simple scoring system using these variables to identify and stratify patients during their index hospitalization. Lay Summary: The one year risk of colectomy in patients hospitalized with ulcerative colitis increases if they are younger than 40-years-old, have used one or more biologic drugs in the past and/or receive an inpatient salvage (step-up) therapy during the hospitalization. Abstract : Predictive factors for colectomy in severe ulcerative colitis include: prior biologic exposure, need for inpatient salvage therapy and younger age.